EXPERIMENTAL DEFINITION OF THE VOLUME DEFORMED STATE AT BROACHING IN TRAPEZOIDAL FIRING-PINS - S. A. Mashekov; N. T. Smaylova; A. E. Nurtazayev (Литьë и металлургия)
The deformed state of the forging was investigated in this work. For its exact specifying the «stepwise deformation method» was used.